Examining the Effect of Using Hard-soled Shoes on Static Balance and Shooting Performance During Air Pistol Shooting - Gözdem Yersu Kaya; İrfan Gülmez (IUC University Press, 2024)
This research aims to evaluate the static balance and swing performance of professional air pistol athletes under different landing conditions. 13 volunteer air pistol athletes (nine women and four men) participated in the research (age: 22 years; height: 161 cm; weight: 67 kg; sports age: 8.7 years; highest competition score: 564 points). Static balance and shooting performance tests were applied to the participants in two different footing conditions: without shoes and with hard-soled shoes. SCATT electronic training system was used to determine shooting performance parameters, and the Tecnobody Pk 252 static balance measurement tool was used to determine foot sole oscillation, travel area, and static balance data. As a result of the evaluations made based on the measurements, it was concluded that elipse area (EA), standard deviation F-B (FBSD), and perimeter (P) parameters were significantly better in the shod condition. In the measurements carried out with and without weapons, average C.o.P. Y (ACoPY) performance was better in the armed condition in both conditions, while in the balance measurements of the participants without shoes, it was concluded that the standard deviation M-L (MLSD) performance was significantly better in the armed condition and no significant difference was found for shooting performance parameters. As a result of the evaluation of the findings, it can be said that whether or not using hard-soled shooting shoes affects balance performance, but its effects on shooting performance are not significant.